Flowering effort and reproductive phenology of intertidal colonizing Zostera marina. (5th November 2022) - Guerrero-Meseguer, Laura; Veiga, Puri; Rubal, Marcos
Abstract: The seagrass Zostera marina can inhabit the intertidal where the variable environmental conditions mean that the seagrass meadows are frequently in a continuous state of colonization, influencing, among others, their phenology and flowering effort. This could be especially notable in the southern limits of the species' distribution, where light exposure and temperature reach extreme values during the warmer seasons. In this study, we evaluate the flowering effort, phenology, photophysiology and vegetative development of recent colonizing Z. marina patches inhabiting the intertidal of a lagoon located near its southern limit of distribution, in the Ria de Aveiro (Portugal). To evaluate the effects of low tide exposure, tidepool and emerged seagrass patches were selected. Results showed short-lived differences in the phenology of the flowering of the patches and in their vegetative development, but in general, the photosynthetic activity, timing of flowering, densities of spathes and flowering shoots were similar in emerged and tidepool patches throughout the entire reproductive period (from June to August). The spathes per flowering shoot and the spathe and flowering shoot densities per unit of area of the colonizing patches were comparable to that obtained in other perennial intertidal meadows of this species and its timing was adjusted to that which occurred in areas of similar latitudes, ending when the temperature exceeded 25 °C. These results imply that intertidal colonizing Z. marina patches can flowering similarly to perennial meadows, regardless of whether or not they are submerged in pools at low tide, which implies a great adaptability of the species to intertidal areas. However, to fully understand the reproductive capacity of Z. marina in the Ria de Aveiro, future studies should determine the capacity of these flowers to form mature seeds, as well as their ability to germinate naturally in the area. Highlights: Colonized eelgrass patches reproduced sexually at the same level than other perennial populations. Low tide exposure did not influence the flowering phenology of colonizing Z. marina . The conservation of colonizing eelgrass meadows is essential to improve its natural recovery at the long-term.